A boundary-value problem for linear PDAEs - Marszałek, Wiesław; Trzaska, Zdzisław W. (Zielona Góra: Uniwersytet Zielonogórski)
We analyze a boundary-value problem for linear partial differential algebraic equations, or PDAEs, by using the method of the separation of variables. The analysis is based on the Kronecker-Weierstrass form of the matrix pencil. A new theorem is proved and two illustrative examples are given.
Keywords: differential algebraic equations; boundary-value problems; linear multivariable systems